2012
DOI: 10.1111/j.1755-3768.2012.4445.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subconjunctival bevacizumab on corneal neovascularization: results of a prospective study

Abstract: Purpose To evaluate the effect of subconjunctival bevacizumab injections in patients with corneal neovascularization resulting from different ocular surface disorders. Methods Prospective case series. Fourteen eyes of 13 patients with corneal neovascularization caused by different ocular surface disorders, such as healed corneal ulcers, long‐standing chronic inflammatory diseases and corneal ischaemia secondary to burn were included. All eyes received a single subconjunctival injection of 2.5 mg (0.1 ml) bevac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Of note, 75% of eyes in the active stage and 67% in the maturation stage showed positive response to the treatment in our study, which is in concurrence with other studies. 4,15 The poorer response in established vessels could possibly be explained by lower inflammation and less dependency on VEGF for survival, highlighting the role and need for combination therapy in such cases. 16,17 The effect of subconjunctival bevacizumab in high-risk corneal grafts with VEGF tissue analysis has not been reported earlier and forms an important arm of our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of note, 75% of eyes in the active stage and 67% in the maturation stage showed positive response to the treatment in our study, which is in concurrence with other studies. 4,15 The poorer response in established vessels could possibly be explained by lower inflammation and less dependency on VEGF for survival, highlighting the role and need for combination therapy in such cases. 16,17 The effect of subconjunctival bevacizumab in high-risk corneal grafts with VEGF tissue analysis has not been reported earlier and forms an important arm of our study.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, 66.6% of the patients showed a decrease in the vessel caliber. In their prospective study, Benayoun et al 15 concluded that bevacizumab acts by creating a vasoconstrictive effect that is evident from the first week reaching its peak after 1 month and suggested that repeated injections would probably strengthen the efficacy of the treatment. This progressive decrease in the vessel caliber with each repeated dose of subconjunctival bevacizumab was also observed in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Although penetration into the cornea in mice is enhanced by epithelial damage, the levels in stroma are less than after subconjunctival injection 19. A prospective uncontrolled study of 12 eyes that received a single subconjunctival injection of 2.5 mg of bevacizumab reported a maximum reduction of not of area of involvement by CoNV after 1 month, with a loss off effect over the subsequent 2 months, although the final reduction was still statistically significant (p=0.02) 14. The study also suggested that the treatment was less effective in cases with established CoNV 14…”
Section: Discussionmentioning
confidence: 99%
“…Экспериментальная и клиническая апробация анти-VEGF-препаратов в лечении неоваскуляризации роговицы подтвердила их относительную безопасность и высокую эффективность, что проявлялось в снижении калибра и количества сосудов, уменьшении зоны инвазии новообразованных сосудов в роговицу [35,46,50,51]. Препараты применялись в виде инстилляций [35,41,46,50] , субконъюнктивальных [41,51,52], интрастромальных, интракамеральных и интравитреальных инъекций [1,3]. При сравнительном анализе эффективности применения местной и субконъюнктивальной форм введения оба способа показали антиангиогенную эффективность, однако местное применение требовало более высоких концентраций препарата [1].…”
Section: ингибиторы Vegfunclassified